ACTIVITY OF BAY LEAF EXTRACT (Eugenia polyantha) AS ANTIINFLAMMATORY IN WHITE RAT (Rattus norvegicus): NARRATIVE REVIEW - Ida Ayu Nadia Kusumastuti; Made Krisna Adi Jaya (Pharmacy Department, Math and Sciences Faculty, Udayana Univerity, 2022)
Background: Inflammation is the body's defense response against foreign body invasion, tissue injury, or both caused by microorganisms, mechanical trauma, chemical compounds, and physical factors. Anti-inflammatory agents can be used to treat inflammation. Bay leaves are one example of a plant that can be used. Ethanol extract and water extract of a bay leaf can be anti-inflammatory because they contain flavonoids. Objectives: The purpose of this study was to see how effective ethanol extract and aqueous extract of bay leaf were as antiinflammatory agents in mice. Methods: This study employs a systematic literature review approach, descriptive qualitative research, and library research. Results: The most efficacious dose was 150 mg/kg BW at a 70 percent concentration and at an 80 percent concentration for ethanol extract of bay leaves, and 50 mg/kg BW for the aqueous extract of bay leaves. Conclusion: Based on the results of this study, it can be concluded that bay leaf (Eugenia polyantha) ethanol extract and aqueous extract have anti-inflammatory activities. Keywords: Anti-inflammatory; Bay Leaf; Diclofenac sodium; Ethanol Extract; Aqueous